Important considerations for craniofacial mapping using laser scanners - Majid, Zulkepli; Chong, A. K.; Setan, Halim (Remote Sensing and Photogrammetry Society, 2007)
The use of a laser scanning system for human craniofacial mapping has gained considerable interest recently as it offers a non-contact method which is very efficient in capturing a vast amount of accurate spatial data. Nonetheless, there is a need for a thorough evaluation to identify the important technical factors which may affect the accuracy of the system. This paper discusses the tests and the results of an evaluation of the Minolta VI-910 3D laser scanning system used to capture craniofacial surface data. The research shows that the factors to consider for craniofacial mapping are: scan distance, camera focal length, laser beam intensity, scanning resolution, convergence angle and number of overlapping scans